Force applied to a grab bar during bathtub transfers. (December 2020) - Guay, Manon; Vinet, Myriam; Bombardier, Anne-Marie; Hamel, Mathieu; Sveistrup, Heidi; Demers, Louise; Smeesters, Cécile
Abstract: Background: Grab bars are a common fall prevention strategy in the bathroom, but biomechanical data are lacking to support clinicians' interventions. This study aims to determine the magnitude and duration of the force applied to four grab bar configurations during complete bathtub transfers on a potentially slippery surface. Methods: A three factorial repeated measures design was used in an experimental environment including a bathtub, padded walls, instrumented fixed grab bars and a safety harness. Seven healthy young adults stepped into the bathtub, sat down at the bottom, stood up and stepped out (three trials), with or without a slippery surface, grabbing onto four grab bar configurations (vertical, angled, horizontal low, horizontal high). Maximum force magnitudes and durations during bathtub transfers were measured by two 6-degrees of freedom load cells. Findings: On average, 23.2 ± 6.4% of body weight was applied on the grab bar during complete bathtub transfers. Maximum resultant forces were not influenced by grab bar configuration, presence of a slippery surface, or direction of bathtub transfer (entrance or exit), except for the vertical configuration without a slippery surface where the maximum resultant force was smaller than for the three other configurations. Transferring on a slippery surface increased the time participants applied force on the grab bars. Interpretation: Grab bars used during complete bathtub transfers with no loss of balance should be capable of sustaining a minimum of 23.2% of body weight, to which a factor of safety of 1.5 should be added, regardless of the grab bar configuration. Highlights: During bathtub transfers, grab bars should sustain at least 23.2% of body weight plus a safety factor of 1.5. Three out of four grab bar configurations did not impact maximum resultant forces. Transferring on a slippery surface increased force duration on the grab bars.